A study of temperature variation in closed cars / Nor Hanim Abdul Rahman, Mohd Rozaiman Aziz and Suzana Ab. Rahim - Abdul Rahman, Nor Hanim; Aziz, Mohd Rozaiman; Ab. Rahim, Suzana (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2005)
This paper emphasizes on the danger of leaving any living things in enclosed car. Various interior temperatures are taken from vehicles parked under direct sunlight. Results show that the most critical time is during the first 20 minutes, where the temperatures can increase to between 15 and 30 degree Celsius from its initial temperature, which is equivalent to between 50% and 100% increments. Results also show that color or size do not necessarily reduce the increment of the interior temperature.